Vitamin D3 treatment differentially affects anxiety-like behavior in the old ovariectomized female rats and old ovariectomized female rats treated with low dose of 17β-estradiol - Julia O. Fedotova (BMC, 2019)
Abstract Background Estrogen deficiency effects on affective-related behavior are restricted to certain periods of age after ovary removal. Among other nutraceuticals, one of such «natural» substances for treatment of affective-related diseases could be vitamin D3. It is a great interest to evaluate the effects of repeated cholecalciferol administration on anxiety-related behavior in the old female rats with long-term estrogen deficiency. The present study was performed to determine the behavioral effects of cholecalciferol treatment at different doses as an adjunctive therapy alone or in a combination with low dose of 17β-estradiol on anxiety-like behavior of the old (16-18 months) female rats at 12 weeks after ovariectomy. Methods Vitamin D3 supplementation individually (as cholecalciferol at doses of 1.0, 2.5 or 5.0 mg/kg/day, s.c.) or in co-administration with of 17β-estradiol (17β-E2, 0.5 μg/rat, s.c.) were given to the old ovariectomized (OVX) rats at 12 weeks after ovariectomy. Anxiety-related state was tested in the elevated plus maze (EPM) and light-dark test (LDT), as well behavioral reactivity was registered in the open field test (OFT). Moreover, 25-hydroxyvitamin D3 levels in the blood serum of these OVX rats treated with Vitamin D3 or Vitamin D3 plus 17β-E2 were measured. Results The results of the present study indicated that Vitamin D3 supplementation at dose of 1.0 mg/kg/day decreased manifestations of anxiety-like profile in the old OVX rats. Treatment with Vitamin D3 (1.0 mg/kg/day) plus 17β-E2 in resulted in more profound anxiolytic-like effects the old OVX rats than effects of both drugs administered alone. Moreover, treatment with cholecalciferol (1.0 mg/kg/day, s.c.) in the old ovariectomized rats after ovariectomy at 12 weeks produced elevated estradiol and 25-OH-VD3 levels for these rats as compared to the old OVX females treated with oil solvent. Conclusions Using the preclinical study, chronic cholecalciferol, 17β-E2 and their combination treatment were shown to be effective for anxiety-like treatment in the old subjects with long-term estrogen deficiency.